2023
DOI: 10.3390/heritage6050219
|View full text |Cite
|
Sign up to set email alerts
|

The Remains of a Manila Galleon Compass: 16th-Century Nautical Material Culture

Abstract: This article reveals the recovery of a compass balance from a Manila galleon that was wrecked in the 16th century off the coast of Baja California, Mexico, and discusses the possibility that it was made in Spain. Based on an analysis of navigation treaties, written in the context of the training of pilots by the Casa de Contratación (House of Trade), it is revealed in detail how nautical compasses were manufactured in Spain during that period. As a result of the review of the nautical literature of that centur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the article "The remains of a Manila Galleon compass: 16th century nautical material culture" by Flor Trejo Rivera and Roberto Junco Sánchez [11], the authors debate the discovery of a compass balance from a Manila galleon that was wrecked off the coast of Baja California, Mexico, and discuss the possibility that it was manufactured in Spain, supporting their research on the analysis of navigation treaties that were written in the context of the training of pilots by the Casa de Contratación (the Spanish board of trade and navigation). Considering both archaeological and documentary evidence, it is concluded that the compass was the most important nautical instrument on board and that its simple design allowed any malfunction to be resolved during journeys.…”
mentioning
confidence: 99%
“…In the article "The remains of a Manila Galleon compass: 16th century nautical material culture" by Flor Trejo Rivera and Roberto Junco Sánchez [11], the authors debate the discovery of a compass balance from a Manila galleon that was wrecked off the coast of Baja California, Mexico, and discuss the possibility that it was manufactured in Spain, supporting their research on the analysis of navigation treaties that were written in the context of the training of pilots by the Casa de Contratación (the Spanish board of trade and navigation). Considering both archaeological and documentary evidence, it is concluded that the compass was the most important nautical instrument on board and that its simple design allowed any malfunction to be resolved during journeys.…”
mentioning
confidence: 99%